Information security architecture an integrated approach to security in the organization - Tudor, Jan Killmeyer (Auerbach Publications, 2006)
Information Security Architecture incorporates the knowledge developed during the past decade that has pushed the information security life cycle from infancy to a more mature, understandable, and manageable state. The book describes in detail every one of the eight ISA components. Each chapter provides an understanding of the component and details how it relates to the other components of the architecture. The text also outlines how to establish an effective plan to implement each piece of the ISA within an organization.